Epistatic and pleiotropic effects of polymorphisms in the fibrinogen and coagulation factor XIII genes on plasma fibrinogen concentration, fibrin gel structure and risk of myocardial infarction - Mannila, Maria Nastase; Eriksson, Per; Ericsson, Carl-Göran; Hamsten, Anders; Silveira, Angela (Thrombosis and Haemostasis, 2006)
An intricate interplay between the genes encoding fibrinogen gamma (FGG), alpha (FGA) and beta (FGB), coagulation factor XIII (F13A1) and interleukin6 (IL6) and environmental factors is likely to influence plasma fibrinogen concentration, fibrin clot structure and risk of myocardial infarction (MI). In the present study, the potential contribution of SNPs harboured in the fibrinogen, IL6 and F13A1 genes to these biochemical and clinical phenotypes was examined. A database and biobank based on 387 survivors ofa first MI and population-based controls were used. Sixty controls were selected according to FGG 9340T>C [rs1049636] genotype for studies on fibrin clot structure using the liquid permeation method. The multifactor dimensionality reduction method was used for interaction analyses. We here report that the FGA 2224G>A [rs2070011] SNP (9.2%), plasma fibrinogen concentration (13.1%) and age (8.1%) appeared as independent determinants of fibrin gel porosity. The FGA 2224G>A SNP modulated the relation between plasma fibrinogen concentration and fibrin clot porosity. The FGG-FGA*4 haplotype, composed of the minor FGG 9340C and FGA 2224A alleles, had similar effects, supporting its reported protective role in relation to MI. Significant epistasis on plasma fibrinogen concentration was detected between the FGA 2224G>A and F13A1 Val34Leu [rs5985] SNPs (p<0.001).The FGG 9340T>C and FGB 1038G>A [rs1800791] SNPs appeared to interact on MI risk, explaining the association of FGG-FGB haplotypes with MI in the absence of effects of individual SNPs. Thus, epistatic and pleiotropic effects of polymorphisms contribute to the variation in plasma fibrinogen concentration, fibrin clot structure and risk of MI.
Keywords: Epistasis; fibrinogen clot structure; myocardial infarction; plasma fibrinogen concentration; pleiotropy